Guns and contemporary society : the past, present, and future of firearms and firearm policy - Utter, Glenn H. (Santa Barbara, California : Praeger, 2016)
"This three-volume set examines various approaches to firearms, including constitutional and legal issues, public health and criminal justice concerns, and perspectives on personal safety and self-defense. Recent mass shootings have led to renewed calls for additional legislation at the state and federal levels to address gun access and control. In this hard-hitting compilation, experts delve into various aspects of firearms in America--from gun control and gun rights to militia movements, to school-related shootings, and to the recent trends in gun ownership by women. Authors from varied backgrounds and viewpoints share their perspectives on the pros and cons of firearm ownership as all of the following: a constitutional right, a key instrument of self-defense, a guarantee of political freedoms, and as a major factor in crime and personal injury. The reference is divided into three volumes. The first volume covers firearm history, legislation, and policy; the second volume explores public opinion, gun ownership trends, international laws, and self-defense; and the third considers popular debates about firearm policy, including concealed carry of firearms, terrorism and the ownership of firearms, background checks for purchasing guns, and stand-your-ground laws. The work concludes with an informed debate on gun policy between Richard Feldman, president of the Independent Firearm Owners, and Paul Helmke, former president of the Brady Campaign to Prevent Gun Violence."--Publisher's description.
V.3. CURRENT CONROVERSIES AND POLICY RECOMMENDATIONS: Preface -- Introduction / Glenn H. Utter -- Weapons in schools / Ronald D. Stephens -- Concealed carry of firearms on university campuses / Robert L. Spinks and Michael C. Powell -- Psychological factors in legal firearms usage / Glenn E. Meyer -- Terrorism and the ownership of firearms / Saundra J. Ribando and Amanda J. Reinke -- How stand-your-ground laws hijacked self-defense / Mary Anne Franks -- Gun violence reduction strategies / Sean Maddan -- Background checks for purchasing firearms / Glenn H. Utter -- Seeking common ground: perspectives of a gun control supporter / Paul Helmke -- Seeking common ground perspectives of a gun rights supporter / Richard Feldman.
Includes bibliographical references and index.
Keywords: Gun control -- United States -- History; Firearms ownership -- Government policy -- United States -- History; Firearms -- United States -- History; Firearms -- Law and legislation -- United States -- History